2008
DOI: 10.1152/ajpregu.00153.2007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between low magnesium status and TRPM6 expression in the kidney and large intestine

Abstract: The body maintains Mg(2+) homeostasis by renal and intestinal (re)absorption. However, the molecular mechanisms that mediate transepithelial Mg(2+) transport are largely unknown. Transient receptor potential melastatin 6 (TRPM6) was recently identified and shown to function in active epithelial Mg(2+) transport in intestine and kidney. To define the relationship between Mg(2+) status and TRPM6 expression, we used two models of hypomagnesemia: 1) C57BL/6J mice fed a mildly or severely Mg(2+)-deficient diet, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 43 publications
6
48
1
3
Order By: Relevance
“…The molecular mechanisms underlying this magnesium wasting in MgL are yet to be fully elucidated; however, dysregulation of TRPM6 in both kidneys and cecum may be important. 33 It is also possible that magnesium wasting and blood pressure elevation may be attributed, at least in part, to renal dysfunction in MgL, because these mice exhibited microalbuminuria (as evidenced by higher urinary albumin:creatinine ratios in MgL compared with MgH mice). When we examined the expression of the Mg transporter TRPM7 in vascular tissue, we observed that aortas from MgL mice have a striking increase in TRPM7 mRNA levels compared with MgH mice.…”
Section: Paravicini Et Al Vascular Structure and Function In Hypomagnmentioning
confidence: 99%
“…The molecular mechanisms underlying this magnesium wasting in MgL are yet to be fully elucidated; however, dysregulation of TRPM6 in both kidneys and cecum may be important. 33 It is also possible that magnesium wasting and blood pressure elevation may be attributed, at least in part, to renal dysfunction in MgL, because these mice exhibited microalbuminuria (as evidenced by higher urinary albumin:creatinine ratios in MgL compared with MgH mice). When we examined the expression of the Mg transporter TRPM7 in vascular tissue, we observed that aortas from MgL mice have a striking increase in TRPM7 mRNA levels compared with MgH mice.…”
Section: Paravicini Et Al Vascular Structure and Function In Hypomagnmentioning
confidence: 99%
“…Colocalization with the sodium-chloride cotransporter confirmed TRPM6 presence within the luminal membrane of DCT cells [13] . Dietary Mg 2+ restriction was shown to increase TRPM6 mRNA and protein expression in the mouse kidney [19,20] , while Mg 2+ supplementation induces TRPM6 expression in the colon [19,20] . TRPM6 expression and Mg 2+ (re)absorption are also regulated by a variety of hormones and compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments conducted on mice indicated that dietary Mg deficiency and hypomagnesemia result in a significant upregulation of TRPM6 channels in the kidneys, whereas a Mg-enriched diet decreases TRPM6 expression (Groenestege et al, 2006;Rondón et al, 2008a;van Angelen et al, 2013). However, upregulation of TRPM6 in pigs fed a diet supplemented with inulin does not necessarily indicate that inulin did not improve the bioavailability of magnesium.…”
Section: Discussionmentioning
confidence: 94%